2021
DOI: 10.2147/vmrr.s317103
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Molecular Detection of Foot and Mouth Disease Virus in Dairy Cattle Around Addis Ababa, Central Ethiopia

Abstract: Background: Foot and mouth disease is a debilitating and highly contagious transboundary disease of cattle that can cause a huge economical loss globally. It is a notifiable disease in Ethiopia, and it is thought to be causing a decrease in cattle productivity and production. Methods: A cross-sectional study and outbreak investigation were performed to estimate seroprevalence, identify associated factors and serotypes of FMDV in dairy cattle around Addis Ababa. A multi-stage random sampling technique was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 40 publications
1
12
1
Order By: Relevance
“…The observed high prevalence in the current study could be attributed to the geographical location of the farms, failure to periodically vaccinate animals, improper management practices, herding of farm animals near to wildlife areas, and contact of animals with livestock of other neighborhoods. On the contrary, seroprevalence documented in this survey showed a much higher value as compared to the previous reports of 10.5% of national prevalence, 9.5% from southern Ethiopia, 8.18% from South Omo, Ethiopia, and 14.05% from Eastern Hararge, Ethiopia by [9,11,49,50], respectively On the other hand, a much higher prevalence than the present study was reported, i.e., 42.7% in Borena, southern Ethiopia by [51], 72.1% in central Ethiopia [18], and 52.5% in Kenya by [52] in cattle. These differences could be related to variation in agroecology, geo-spatial distribution of the disease, possible sampling after an outbreak, and variations in the production/herding systems among the areas of the study.…”
Section: Seroprevalence and Factors Associated With Fmd Sero-positivi...contrasting
confidence: 88%
See 2 more Smart Citations
“…The observed high prevalence in the current study could be attributed to the geographical location of the farms, failure to periodically vaccinate animals, improper management practices, herding of farm animals near to wildlife areas, and contact of animals with livestock of other neighborhoods. On the contrary, seroprevalence documented in this survey showed a much higher value as compared to the previous reports of 10.5% of national prevalence, 9.5% from southern Ethiopia, 8.18% from South Omo, Ethiopia, and 14.05% from Eastern Hararge, Ethiopia by [9,11,49,50], respectively On the other hand, a much higher prevalence than the present study was reported, i.e., 42.7% in Borena, southern Ethiopia by [51], 72.1% in central Ethiopia [18], and 52.5% in Kenya by [52] in cattle. These differences could be related to variation in agroecology, geo-spatial distribution of the disease, possible sampling after an outbreak, and variations in the production/herding systems among the areas of the study.…”
Section: Seroprevalence and Factors Associated With Fmd Sero-positivi...contrasting
confidence: 88%
“…Statistical inference was difficult, as the sample sizes between groups differ and are small. The chance of being sero-positive was higher in adult animals (>18 months) with OR: 6, 95 % CI, [2,18] as compared to their younger counterparts. Caprine species were seen to have 3.8% sero-positivity, but the chance was eight times higher (OR: 8, 95% CI, [3,22]) for ovine as compared to caprine.…”
Section: Sero-prevalence Of Fmd In Domestic Small Ruminantsmentioning
confidence: 95%
See 1 more Smart Citation
“…These serotypes are reported frequently from one part or another part of the world. The low infectious dose of the virus, rapid replication, prolonged environmental survival, the incubation period of 7-14 days, and high virus titer in nasal secretions contributes to the rapid transmission of the virus to the susceptible animal population [7]. The disease-causing ability of FMDV is different for different animals, which may depend on different factors such as the duration of virus present in the body, abrasion through which virus enters the body, and release of virus titer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Besides animal-animal transmission via respiratory aerosols, the virus is disseminated easily via mechanical routes, i.e., fomites, shoes, clothes, vehicles, and veterinary surgical instruments. Furthermore, the uncontrolled transboundary movements of animals have also aggravated its spread [7].…”
Section: Introductionmentioning
confidence: 99%